Enhancing endurance performance by nutritional manipulation: A sleep low strategy - Marquet, L. A.; Louis, J.; Tiollier, E.; Hawley, J.; Burke, L.; Brisswalter, J.; Hausswirth, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: For several years, a growing interest is brought on the manipulation of carbohydrate (CHO) availability before and after specific training sessions. This strategy could promote the physiological adaptations to training and enhance endurance performance (Burke, 2010). Within this context, the purpose of this study was to test the effects of a low glycogen availability doubly induced by training and nutrition manipulation. A new "sleep low" strategy was experimented, including blocs of variable intensity training sessions performed at night and after an overnight fast. Methods: During 3 consecutive weeks, 23 well-trained triathletes (age: ± years;; maximal oxygen uptake: 61.2 ± 4.8 ml/min/kg) volunteered to follow a standardized training program and specific nutritional guidelines according to the group where they were assigned. Each week, all participants performed the same standardized training program, including low intensity training sessions (LIT) in the morning and high intensity training sessions (HIT) at the end of the afternoon over 4 consecutive days. Only one LIT session per day was prescribed for the others days of the week in order to maintain a 12-15h training volume. In the "sleep low" group (SL=13), no CHO intake was authorized for all HIT and LIT sessions. The diner was also CHO-free and the LIT sessions were performed after an overnight fast so that they trained with a low CHO availability. At the opposite, the CHO availability was regularly maintained in the "sleep high" group (SH=10) by consuming sports drinks during training sessions and CHO at every meals. Finally all groups ingested the same amount of CHO per day (6 g/kg/d) but divided differently over the day. Performances in cycling (submaximal and supramaximal tests) and running (10km test), perceived exertion, cycling efficiency and body composition were recorded before and after the 3 weeks of modified training and nutrition. Changes in studied variables over time and between groups were assessed by using a magnitude-based inference approach recommended for studies in sports medicine and exercise sciences. Results: A significant enhancement in cycling (+7.2% time to exhaustion) and running performances (-56s on 10km) were recorded at the end of the protocol only in the SL group. These changes in performances were associated with a 1% reduction in fat mass (-795g). We hypothesized potential beneficial changes in cycling efficiency by lowering the oxygen consumption at a given intensity, and a preservation of glycogen stocks in the SL group. (The present study is still running and data presented in this abstract are preliminary results). Conclusion: A chronic "sleep low" training strategy is effective in enhancing endurance performance in cycling and running. Training with low glycogen availability may enhance physiological adaptations involved in endurance performance.